Development of a juçara and Ubá mango juice mixture with added Lactobacillus rhamnosus GG processed by high pressure. (April 2017) - Moreira, Rosângela Maria; Martins, Maurilio Lopes; Leite Júnior, Bruno Ricardo de Castro; Martins, Eliane Maurício Furtado; Ramos, Afonso Mota; Cristianini, Marcelo; Campos, André Narvaes da Rocha; Stringheta, Paulo César; Silva, Vanessa Riani Olmi; Canuto, John Warnens; Oliveira, Dairo Cabral de; Pereira, Danielle Cunha de Souza
Abstract: This study evaluated the development of a juçara and Ubá mango juice mixture and the influence of pasteurization, high isostatic pressure (HIP) and the addition of a probiotic culture of Lactobacillus rhamnosus GG on the physicochemical, microbiological, functional and sensory characteristics of the products obtained. The pasteurized juices (82 °C/1 min) showed larger amounts of total phenolics, greater antioxidant capacity and lower lipid levels as compared to juice processed using HIP (600 MPa/5 min/25 °C). Juice with added L. rhamnosus GG differed with respect to pH, acidity and proteins as compared to those without, due to the fermentative action of the probiotic bacteria. The addition of L. rhamnosus GG to the juice did not affect its acceptance. The levels of L. rhamnosus above 10 8  CFU/mL during the 30 days of storage at 4 °C, demonstrate its viability in this product, which is potentially probiotic. In addition, consumers preferred the juice processed by HIP. Highlights: High isostatic pressure process did not cause a change in the anthocyanin content. The levels of the Lactobacillus rhamnosus GG being above 10 8  CFU/mL during the 30 days at 4 °C. The addition of Lactobacillus rhamnosus GG to the juice did not affect its acceptance. The consumers preferred the juice processed by high isostatic pressure.